(3JfGRY GdbhGfjf aj eLGd Mb GdeDda (B/s - (3CMeO eMeO jhSa GdTMjs; (3CTQa haG eMeOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JfGRY GdbhGfjf aj eLGd Mb GdeDda jbJVj OQGSI Tbjf QFjSjjf hgeG GdbGfhf GdhGLH GdJWHjb ajeG jJYdb HJMOjO GdeDda hgh eG JeJ OQGSJg aj GdHGH GdChd hbO NdUfG efg Edi ENJdGa GdfXe aj JMOjO GdbGfhf GdhGLH GdJWHjb aj JMOjO GdeDda HGNJdGa GdfXe aj JYQja GdeDda , hgPG GdENJdGa jfbSe Mhd bGfhf GdOhdI GdeWdhH JbQjQ GdMeGjI HgG hbGfhf GdOhdI GdCUdjI Ch eG jYQa HbGfhf OhdI GdfTQ GdChd hbO NdUfG Edi Cf CfSH GdbhGfjf ddJWHjb aj JMOjO GdeDda gh bGfhf OhdI GdfTQ GdChd(B. (3CeG GdTb GdKGfj agh OQGSI GdbGfhf GdhGLH GdJWHjb Ydi Mb GdeDda hbO JeJ OQGSJg aj GdHGH GdKGfj ef gPg GdQSGdI hbO NdUfG ajg Edi ENJdGa GdbGfhf HENJdGa GdWQjbI GdJj Je GdEYJOGA ajgG Ydi Mb GdeDda aEf cGf habG ddeSDhdjI GdEJaGbjI aGdbGfhf GdhGLH GdJWHjb aj gPg GdMGdI gh bGfhf GdEQGOI ceG gh GdMGd aj SGFQ GdYbhO, CeG aj GdMGdGJ GdJj jJe GdEYJOGA ajgG Ydi Mb GdeDda habG ddeSDhdjI GdJbUjQjI aGdbGfhf GdhGLH GdJWHjb aj gPg GdMGdI gh bGfhf GdOhdI GdeWdhH JbQjQ GdMeGjI HgG Ydi eG jQO YdjgG ef ESJKfGA aj HYV GdMGdGJ ceG dh cGfJ eOI MeGjI GdMb aj bGfhf GdOhdI GdeWdhH JbQjQ GdMeGjI HgG CWhd ef GdeOI GdebQQI aj bGfhf GdOhdI GdCUdjI(B.s
(3CWQhMI (B((3eGLSJjQ(B)(3, LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdOhdj (B2009s
(3HHdjhLQGajG(B: (3UaMGJ (B218-226s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3Mb GdeDdas; (3GdYed GdPgfjs; (3GdMb GdeGdj ddeDdas; (3bGfhf GdbGVjs; (3bGfhf GdOhdI GdCUdjIs; (3MeGjI Mb GdeDdas; (3GdYbO GdOhdjs; (3JfGRY GdbhGfjf ajeG jJYdb HMb GdeDdas; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs